Transcatheter salvage of dying Glenn – An innovative strategy for postGlenn thrombosis - Shantanu Jain; Debasree Gangopadhyay; Sabharisundaravel Paulraj; Mahua Roy; Jayitri Mazumdar; Joyeeta Dutta (Annals of Pediatric Cardiology)
PostGlenn thrombosis is an infrequent, serious complication requiring immediate attention, which is not uncommon in a resource-limited setting where patients are often lost to follow-up and have poor compliance with medications. This rare complication has infrequently been reported in the past. We describe a case of a massive thromboembolic event in a patient presenting acutely in a decompensated state 14 years after initial palliation by Glenn shunt. We report an innovative strategy of using transcatheter mechanical thrombectomy using a rotational thrombectomy device and chemical thrombolysis for the successful salvation of the Glenn circuit.